Manufacturing transformation : comparative studies of industrial development in Africa and emerging Asia - Newman, Carol, 1977- (Oxford : Oxford University Press, 2016)
This volume presents results of comparative country-based research that sought to answer a seemingly simple but puzzling question: why is there so little industry in Africa? It brings together detailed country case studies of industrial policies and industrialisation outcomes in eleven countries, conducted by teams of national researchers in partnership with international experts on industrial development - providing analysis of the contemporary industrialisation experience in low-income Africa.
This edition previously issued in print: 2016.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 15, 2016).
Keywords: Industrialization -- Africa; Industrialization -- Asia